Genetic characterization of dengue virus type 1 isolated in Brunei in 2005-2006 - Osman, O.; Fong, M.Y.; Sekaran, S.D. (Society for General Microbiology, 2009)
The full-length genomes of two DENV-1 viruses isolated during the 2005-2006 dengue incidents in Brunei were sequenced. Twenty five primer sets were designed to amplify contiguous overlapping fragments of approximately 500-600 base pairs spanning the entire sequence of the genome. The amplified PCR products were sent to a commercial laboratory for sequencing and the nucleotides and the deduced amino acids were determined. Sequence analysis of the envelope gene at the nucleotide and amino acid levels between the two isolates showed 92 and 96 identity, respectively. Comparison of the envelope gene sequences with 68 other DENV-1 viruses of known genotypes placed the two isolates into two different genotypic groups. Isolate DS06/210505 belongs to genotype V together with some of the recent isolates from India (2003) and older isolates from Singapore (11990) and Burma (11976), while isolate DS212/110306 was clustered in genotype IV with the prototype Nauru strain (11974) and with some of the recent isolates from Indonesia (2004) and the Philippines (2002, 2001). In the full-length genome analysis at the nucleotide level, isolate DS06/210505 showed 94 identity to the French Guyana strain (11989) in genotype V while isolate DS212/110306 had 96 identity to the Nauru Island strain (11974) in genotype IV. This work constitutes the first complete genetic characterization of not only Brunei DENV-1 virus isolates, but also the first strain from Borneo Island. This study was the first to report the isolation of dengue virus in the country.